Cultivation prospect of medicinal plants in Bangladesh: experiences from Natore - Sharmin, Lammia (BRAC Research and Evaluation Division (RED), 2020)
The study aimed to explore the possibility of medicinal plant cultivation as a sustainable livelihood option. The study was conducted among the medicinal plant cultivators of five villages of Laxmipur union of Natore sadar upazila in Natore district. Both qualitative and quantitative approaches were used. Data were collected during February-April 2004 from both primary and secondary sources. The findings show that the farmers were motivated to cultivate medicinal plants because of its profitability. The cost-benefit analysis of some of the medicinal plants also supported this. But the market of the medicinal plants is still in a pre-mature stage. A linkage between the cultivators and the herbal medicine or cosmetic producers could definitely help develop the medicinal plant cultivation prospect.